Podul peste Tisa - Stanculescu, Ileana (Germany : Stanculescu, Ileana, 2004)
Bridges connect people, unless it is forbidden to cross them. And that is exactly what is happening with the recently rebuilt bridge across the river Tisza, which is supposed to bring together relatives, friends and former neighbours who got divided throughout history by various political divisions. The old bridge between Sighet, a Rumanian town, and Slatina, a Ukrainian town, was destroyed by the German troops during World War II. After the war, the northern bank of the Tisza River became part of the Soviet Union, while the southern bank continued to be Rumanian, and the border was closed. The Tisza River separated the two towns for almost fifty years. After the collapse of the Soviet Union, Slatina became a Ukrainian town and the border was reopened. The old bridge has now been rebuilt in three years with the help of the European Union. But what for? Nobody is allowed to cross it yet. The second round of admittance of new members to the E.U. will include Rumania but exclude the Ukraine. So, friends and family members can only communicate by shouting across the river. It is with such a scene that this interesting, investigative documentary starts, confronting us immediately with the absurdity of political reasoning. (IDFA)
Supported by OSI-Budapest Arts and Culture Program.
Duration: 01:15:00
Keywords: Documentary films